Digital games use in entrepreneurhip education at the undergraduate level: a systematic review - Alghamdi, Ebtehal (Journal of Management and Business Education, 2023)
Past reviews on digital games use in entrepreneurship education failed to provide detailed information on how researchers employed gameplay in learning models. Additionally, prior reviews have inadequately examined the methodological rigor and the distributional characteristics of articles within such an area. This systematic review provides information about the geographic spread and breadth of digital games use in entrepreneurship education literature. More importantly, the current analysis provides in depth assessment of the methodological attributes of published articles in the discipline. Based on the comprehensive evaluation, future research directions are suggested to strengthen this area of study.